Uso da farinha mista de inhame (Dioscorea alata) e gergelim (Sesamun indicum L.) na formulação de bolos de alto valor nutricional - Bamberg, Carla Parish (2011)
The objective of the present study was designed to evaluate the process of obtaining mixed flour by adding yam (Dioscorea sp) and sesame (Sesamun indicum L.) and using such mixed flour in preparation of cakes served in school meals, analyzing its nutritional value and sensorial characteristics. In the experimental design parts of wheat flour used in the cakes was substituted by yam flour (15, 25 e 35%) and sesame flour (2,5, 5 e 7,5%), totaling 100% of mixed flour. The methodology utilized adopted concentrations delimited by factorial planning, being the response variable for the attributes of the sensorial analysis. Regarding physical-chemical characteristics of mixed flour, Yam and Sesame the average results obtained were 11.54%, 0.92% 10.64% 3.83% 4.20% 69.35% and 354, 45kcal/100 g, for moisture, ash, protein, lipids, carbohydrates, fiber, and energy, respectively. The sensorial tests were performed by 62 untrained tasters who evaluated color, texture, aroma, taste and overall impression. All cake formulations made with the mixed flour were well accepted for taste and overall impression and the evaluated attributes reached an average higher than 6.0, which is on the positive side of the evaluation scale, proving that partial substitution of wheat flour by yam and sesame flour had good acceptance. The highest averages were obtained in the evaluation of aroma (6.93), flavor (7.41) and overall impression (7.06). The formulation with 15% of yam flour and 7,5% of sesame flour presented best acceptance. In these conditions, the production of cakes with mixed flour is a viable option from the stand point of product acceptance.